2018
DOI: 10.1186/s13104-018-3453-z
|View full text |Cite
|
Sign up to set email alerts
|

Response to flutamide, as second-line therapy after bicalutamide, predicts efficacy of abiraterone, not that of enzalutamide

Abstract: ObjectiveThe objective of this retrospective study was to evaluate whether the effect of second-line therapy of flutamide after bicalutamide can predict the response to abiraterone.ResultsThirty-four patients received abiraterone and 32 received enzalutamide after treatment with second-line flutamide for castration-resistant prostate cancer. Prostate-specific antigen-progression-free survival during treatment with abiraterone or enzalutamide was the endpoint. The response to flutamide therapy was defined as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Nakai et al, have reported that patients using abiraterone as the first novel androgen receptor targeted agent and showing a good response to flutamide therapy following initial MAB using bicalutamide therapy, had a significantly higher PSA-PFS rate and % PSA change compared to those without such response. However, multivariate analysis for the predictive factor of PSA-PFS was not performed in this study (12). From the above results, it was considered that the efficacy of alternative antiandrogen therapy using flutamide in CRPC patients could be a predictor of subsequent enzalutamide therapy.…”
Section: During Therapy With Novel Androgen Receptortargeted Agents (Enzalutamide or Abiraterone) Waterfall Plots In Patients Who Receivementioning
confidence: 92%
See 2 more Smart Citations
“…Nakai et al, have reported that patients using abiraterone as the first novel androgen receptor targeted agent and showing a good response to flutamide therapy following initial MAB using bicalutamide therapy, had a significantly higher PSA-PFS rate and % PSA change compared to those without such response. However, multivariate analysis for the predictive factor of PSA-PFS was not performed in this study (12). From the above results, it was considered that the efficacy of alternative antiandrogen therapy using flutamide in CRPC patients could be a predictor of subsequent enzalutamide therapy.…”
Section: During Therapy With Novel Androgen Receptortargeted Agents (Enzalutamide or Abiraterone) Waterfall Plots In Patients Who Receivementioning
confidence: 92%
“…using flutamide affect the efficacy of novel androgen receptor-targeted agents. Only a few reports have evaluated the relationship between the therapeutic effects of alternative anti-androgen therapy using flutamide and the subsequent treatment effect of novel androgen receptor-targeted agents (12,13). In the present study, we reviewed the clinical characteristics of 79 patients and examined the clinical benefits of flutamide as an alternative anti-androgen agent and as an effective predictor of novel androgen receptortargeted agents.…”
Section: During Therapy With Novel Androgen Receptortargeted Agents (Enzalutamide or Abiraterone) Waterfall Plots In Patients Who Receivementioning
confidence: 99%
See 1 more Smart Citation
“…Zhao et al (4) reported that switching to flutamide did not influence the OS of abiraterone acetate in patients with metastatic CRPC, which suggests that the OS of patients with CRPC may be prolonged based on the response duration of alternative anti-androgen therapy. Nakai et al (28) showed that patients for whom second-line flutamide was effective had a better response to subsequent abiraterone acetate than those for who the treatment proved to be ineffective. In a preclinical setting, Prekovic et al (29) showed that the combination of the androgen receptor (AR) F877L mutation, which leads to enzalutamide resistance, and the AR T878A mutation, which is often found in flutamide-treated patients, causes enzalutamide to have strong agonistic activity, but that only the F877L mutation has a weak effect on enzalutamide binding, which suggests that the prior administration of flutamide may enhance enzalutamide resistance.…”
Section: Any Psa Decline ≥50% Psa Decline ---------------------------mentioning
confidence: 99%
“…One potential suppressive agent is nonsteroidal antiandrogen flutamide, which exerts effects by interfering with the binding of dihydrotestosterone or testosterone to the androgen receptor 4 . Currently, there are indications that flutamide as a second‐line hormonal therapy decreases adrenal androgens and is effective for bicalutamide‐refractory prostate cancer 5 …”
Section: Introductionmentioning
confidence: 99%